Comparative study on corrosion characteristics of conductive concrete in red soil environment. - Shan Lin; Xu Tian; Feng Pei; Pinghao Yang; Hongbo Cheng (PLoS ONE)
In order to solve the corrosion problem of grounding materials in highly corrosive red soil environments, conductive concrete was proposed as a new type of grounding material. The corrosion resistance of conductive concrete was tested and compared to select a suitable preparation scheme with excellent corrosion resistance. A series of conductive concrete samples were made using different conductive materials such as graphite, stainless steel fiber (SSF), and ordinary silicate concrete. Common grounding metals include Q235 steel and galvanized steel, embedded in red soil, conventional concrete, and conductive concrete. The open circuit potential, dynamic potential polarization, and electrochemical impedance spectroscopy of these metals were measured and analyzed. The open-circuit potential of metal electrodes in red soil is lower than that in concrete, and the potential of specimens with conductive phase is higher than that of the ordinary concrete, show that the corrosion sensitivity of metals in conductive concrete is greatly reduced, the corrosion potential is the lowest and the corrosion current is the highest in red soil, the capacitance arc radius in red soil is very small, indicating poor corrosion resistance of grounding metals in a red soil environment. All these indexs indicate that using conductive concrete as grounding material can effectively slow down the corrosion of grounding materials in red soil. Compared with stainless steel based conductive concrete, graphite based conductive concrete provides better protection for the grounding metal wrapped around it. As the content of conductive phase materials increases, the corrosion tendency and corrosion rate of conductive concrete decrease. Compared with Q235 carbon steel, galvanized steel exhibits excellent corrosion resistance in conductive concrete. Therefore, it is recommended to use galvanized steel conductive concrete as the grounding material for power systems in red soil environments.